Application of Mahalanobis-Taguchi System in Full Blood Count of Methadone Flexi Dispensing Program - S. K. M., Saad; S. N. A. M., Zaini; M. Y., Abu (Penerbit Universiti Sultan Zainal Abidin, 2022)
Patient under methadone flexi dispensing (MFlex) program are required to do blood tests like full blood count (FBC). A doctor assesses 3 parameters like haemoglobin, platelet count, and fasting blood sugar to ensure the patient has FBC problem. The existing system does not have a stable ecosystem towards classification and optimization. The objective of this study was to apply Mahalanobis-Taguchi system (MTS) in the MFlex program. The data was collected at Bandar Pekan clinic with 34 parameters in the blood tests where 17 parameters in FBC, 8 parameters in liver function profile, 4 parameters in lipid profile, and 5 parameters in renal profile. Two types of MTS methods were used like RT-Method and T-Method for classification and optimization, respectively. As a result, the average Mahalanobis distance (MD) of healthy and unhealthy are classified using RT-Method with 1.00 and 187.06 respectively. Moreover, the significant parameters are evaluated using T-Method with 10 parameters of positive degree of contribution. 15 unknown samples have been diagnosed using MTS by using different positive and negative degree of contribution values to achieve lower MD. Type 2 of 6 modifications has been selected as the best proposed solution as it shows the highest MD value than others which is nearest to the positive value. In conclusion, a pharmacist from Bandar Pekan clinic admitted that MTS is able to solve problems in classification and optimization of MFlex program.